Effect of Irrigation with Treated Wastewater on Squash Yields, Soil Chemical and Microbial Properties - Khazaleh, Hasan; Abu-Awwad, Ahmad; AlQinna, Mohammed (Jordan Journal of Agricultural Sciences, 2023)
n this study, the effects of irrigation with treated wastewater (TWW) on soil chemical, microbiological, and yield of squash were investigated. Squash seedlings (Cucurbita pepo) were irrigated using conventional irrigation water (CIW), treated wastewater (TWW), and blended irrigation water (BIW). The drip irrigation system was used to irrigate Squash with CIW, TWW, and BIW. The concentration of all chemical and microbial irrigation water characteristics was falling within the limits of Jordanian standards (JS893/2021), except for turbidity and boron. Pathogens indicators such as Salmonella, and Helminth eggs were not found in TWW. TWW-irrigated plots had significant differences in electrical conductivity, organic carbon, total nitrogen, and sodium adsorption ratio (SAR). Total coliform and Escherichia coli (E. coli) contents increased significantly within TWW-irrigated plots. Squash’s fresh yield weight irrigated with TWW showed no significant difference compared with CIW. TWW and BIW treatments had a tendency toward lower fruit numbers than CIW. E. coli was not significantly different on the surface of squash fruits, while Total coliform increased significantly for fruits within the TWW-irrigated plots.